Adult heart transplantation with distant procurement and ex-vivo preservation of donor hearts after circulatory death: a case series. Issue 9987 (27th June 2015) - Dhital, Kumud K; Iyer, Arjun; Connellan, Mark; Chew, Hong C; Gao, Ling; Doyle, Aoife; Hicks, Mark; Kumarasinghe, Gayathri; Soto, Claude; Dinale, Andrew; Cartwright, Bruce; Nair, Priya; et al.
Summary: Background: Orthotopic heart transplantation is the gold-standard long-term treatment for medically refractive end-stage heart failure. However, suitable cardiac donors are scarce. Although donation after circulatory death has been used for kidney, liver, and lung transplantation, it is not used for heart transplantation. We report a case series of heart transplantations from donors after circulatory death. Methods: The recipients were patients at St Vincent's Hospital, Sydney, Australia. They received Maastricht category III controlled hearts donated after circulatory death from people younger than 40 years and with a maximum warm ischaemic time of 30 min. We retrieved four hearts through initial myocardial protection with supplemented cardioplegia and transferred to an Organ Care System (Transmedics) for preservation, resuscitation, and transportation to the recipient hospital. Findings: Three recipients (two men, one woman; mean age 52 years) with low transpulmonary gradients (<8 mm Hg) and without previous cardiac surgery received the transplants. Donor heart warm ischaemic times were 28 min, 25 min, and 22 min, with ex-vivo Organ Care System perfusion times of 257 min, 260 min, and 245 min. Arteriovenous lactate values at the start of perfusion were 8·3–8·1 mmol/L for patient 1, 6·79–6·48 mmol/L for patient 2, and 7·6–7·4 mmol/L for patient 3. End of perfusion lactate values were 3·6–3·6 mmol/L, 2·8–2·3 mmol/L, and 2·69–2·54 mmol/L, respectively, showing favourable lactate uptake. Two patients needed temporary mechanical support. All three recipients had normal cardiac function within a week of transplantation and are making a good recovery at 176, 91, and 77 days after transplantation. Interpretation: Strict limitations on donor eligibility, optimised myocardial protection, and use of a portable ex-vivo organ perfusion platform can enable successful, distantly procured orthotopic transplantation of hearts donated after circulatory death. Funding: NHMRC, John T Reid Charitable Trust, EVOS Trust Fund, Harry Windsor Trust Fund.